The Effectiveness of Anti Smoking Campaign Based on Customers Perception Toward Smoking and Anti Smoking Campaign - Hanifi, Raedi Zulfahmi; Wandebori, Harimukti (Journal of Business and Management, 2015)
Abstract - Smoking prevalence in Indonesia has been major problem for many decades. Eventhough anti smoking campaign has been implemented, yet the effectiveness is still in question.This study will explore how customers perception toward smoking and anti smoking campaign may exhibit different impact on effectiveness of anti smoking campaign. Anti smoking campaign or also called demarketing of smoking, is conducted in three fronts. Which are, mass media communication, regulatory meassures, and public opinion. Mass media communication via message framing is use to stir customer perception. Regulatory meassures serve as limitation to smoking activity. Public opinion create unfavorable atmosphere to smoking. The main purpose of this study is to examine how the three fronts of demarketing may influence customer perception and intention to avoid smoking. The final project is limited in the scope of data. The data were gathered in Bandung, Indonesia. A survey with judgment sampling was conducted to 178 respondents,Ã‚Â the respodents also limted to 89 smokers and 89 non smokers. In addition, some interview also being made to provide additional explanation of each data analysis. Descriptive analysis, Independent Sample analysis, and Regresion analysis were used to evaluate data and make data analysis. Furthermore, an analysis of current condition of anti smoking campaign in Indonesia were also provided. The result reveal that perception toward smoking from smoker group is more supportive to smoking rather non smoker group; both groups perception toward anti smoking campaing are same, which are its weak; anti smoking advertisement with positive framing have better impact rather than negative ones; and also regulatory meassures need improvement in terms of implementation to reduce smoking prevalence in Indonesia. Research implications and future research directions conclude the study report. Keywords: Smoking prevalence, Anti smoking campaign, Perception, Message framingÃ‚Â